AB1406-HPR Relationship between knee muscle strength, pain and functional outcomes in patients with patellofemoral osteoarthritis. (12th June 2018) - Guney Deniz, H; Tan, F.; Atilla, B.
Abstract : Background: Knee Osteoartritis (OA) is one of the most common musculoskeletal disorders that adversely affect the functional levels of the patients. Traditionally, knee OA is considered as a problem at the medial compartment of the tibiofemoral (TF) joint. However, OA in patellofemoral (PF) joint can be seen around%25 of the patients. Since the biomechanics of PF joint are distinct from TF joint, the functional assessments specific to PF joint should be considered for PFOA patients. Objectives: The aim of the study was to investigate the relationship between quadriceps femoris strength differences between PFOA patients and control group. Another aim was to define the relationship between pain, knee muscle strength, and functional outcomes in PFOA. Methods: Twenty-five patients with PFOA (age=52.1 years, BMI=26.2 kg/cm 2 ) and 20 age-matched controls (age=54.1 years, BMI=26.1 kg/cm 2 ) were included in the study. The patients diagnosed with PFOA if they had a radiographic Kallgren and Lawrence score grade 2 or 3 in the PF joint, which was greater than KL score for the TF compartments. Pain level was measured with Visual Analogue Scale. The quadriceps femoris and hamstring isometric muscle strengths at 20° and 60° of knee flexion were measured with a hand-held dynamometer. The functional levels of the patients were determined with Kujala Patellofemoral Score and Western Ontario McMaster Universities Osteoartritis Index (WOMAC). Student t-test was used for the comparison of quadriceps strength between PFOA and control groups. Spearman correlation test was used to determine the relationship between pain, muscle strength and functional outcomes. Results: The quadriceps strength at 20° (p=0.03) and 60° (p=0.01) of knee flexion were lower in PFOA group when compared to control group. Hamstring strength at both angles was similar between groups (p>0.05). There were negative correlations between quadriceps muscle strength at 60° knee flexion and pain levels (r=−0.54, p=0.02) and total WOMAC score (r=−0.33, p=0.01). The quadriceps muscle strength at 20° knee flexion was only correlated with Kujala score (r=−0.47, p=0.01). There were no correlations between hamstring strength with pain and functional outcomes (p>0.05). Conclusions: PFOA patients had significantly lower quadriceps strength than control group. Pain level, quadriceps muscle strength and functional outcomes were associated with each other in patients with PFOA. These findings suggest that interventions that have been designed to reduce pain and to improve function should be specific to the affected compartment in knee OA. Reference: [1] Hinman RS, Crossley KM. Patellofemoral joint osteoarthritis: an important subgroup of knee osteoarthritis. Rheumatology (Oxford). 2007;46(7):1057–62. Disclosure of Interest: None declared